Aloe Vera as an Alternative Energy Source - Sihombing, Dewa Alvario; Yulianti, Lisna; Prima, Eka Cahya (Universitas Pendidikan Indonesia (UPI), 2021)
Energy is a basic human need. In Indonesia, fuel oil (BBM) is the most widely used energy source in meeting national energy needs. The composition of Indonesia's national energy consumption in 2015, namely BBM: 52.50%; Gas: 19.04%; Coal: 21.52%; Water: 3.73%; Geothermal: 3.01%; and New Energy: 0.2% (Kholiq, 2015). To reduce the use of non-renewable energy, we are trying to find a solution to overcome this problem, namely by using Aloe vera as a source of electrical. This research focuses on the type of circuit and the number of sets of electrodes to produce an optimal source of electrical energy. In this research, we are using an experimental method that aims to determine whether Aloe vera can be an alternative renewable energy source. The first condition is one leaf, series circuit. The second condition, two leaves with a parallel circuit. The third condition, three-leaf with a parallel circuit. The results of this study are that the more electrodes, the more voltage is generated. By assembling in parallel, the resulting current is greater. From our study, we hopeÂ Aloe veraÂ has potential as an alternative energy source and it can reduce the use of non-renewable energy.